2007
DOI: 10.3892/or.18.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of p21WAF1/CIP1, p16INK4a and CD44s in tongue cancer

Abstract: Abstract. The role of lost or reduced expression of p21, p16 and CD44s in the survival of tongue cancer patients was investigated. Tumours and adjacent non-tumour epithelia (ANTE) from 36 patients with tongue cancer were retrospectively studied by immunohistochemistry using monoclonal antibodies against p21, p16 and CD44s proteins. Expression of p21, p16 and CD44s and their relationship with clinical and pathological parameters were analyzed. Of 36 patients, 12 (33.33%) developed recurrence and 12 died of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…(16) had already shown independent prognostic value for p16 expression in carcinomas of the tongue: its absence was correlated with lower OS and DFS. Other authors failed, however, to demonstrate the influence of this protein on the prognosis (46, 47). When we evaluated survival by tumour extension score, the differences obtained were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…(16) had already shown independent prognostic value for p16 expression in carcinomas of the tongue: its absence was correlated with lower OS and DFS. Other authors failed, however, to demonstrate the influence of this protein on the prognosis (46, 47). When we evaluated survival by tumour extension score, the differences obtained were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 has been shown to be a major factor in cell-cell and cell-ECM interactions, including cell migration, adhesion, and some lymphocyte functions 33 . The low expression of CD44s on tumour cells has been significantly correlated with poor prognosis in tongue carcinomas 24 , and the absence of CD44v expression has been associated with a shorter survival time in lip OSSC 22 . Similarly, KOSUNEN et al 33 has shown that the irregular expression of CD44 in OSCC was correlated with poor DFS and OS.…”
Section: Cd44mentioning
confidence: 99%
“…Other studies, however, did not find any relationship between expression of p16 INK4a and clinical-pathologic stages, 34,35 survival, 36,37 or relapse. 38 This suggests a possible relationship between the lack of protein expression and reduction in the degree of keratinization and differentiation. 36 For Bova et al, 39 the loss of p16 INK4a expression is associated with a reduction in 5-year disease-free survival and, especially, 5-year overall survival.…”
Section: Discussionmentioning
confidence: 97%